Partitioning of integrated energy fluxes in four tail reconnection events observed by Cluster. Issue 12 (17th December 2016) - Tyler, Evan; Cattell, Cynthia; Thaller, Scott; Wygant, John; Gurgiolo, Chris; Goldstein, Melvyn; Mouikis, Christopher
Abstract: We present the partitioning of integrated energy flux from four tail reconnection events observed by Cluster, focusing on the relative contributions of Poynting flux, electron, H+ and O+ enthalpy, and kinetic energy flux in the tailward and earthward directions in order to study temporal and spatial features of each event. We further subdivide the Poynting flux into three frequency bands to examine the possible structures and waves that contribute most significantly to the total Poynting flux from the reconnection region. Our results indicate that H+ enthalpy flux is often dominant, but O+ enthalpy, electron enthalpy, Poynting flux, and H+ kinetic energy flux can contribute significant or greater total energy flux depending on spacecraft location with respect the current sheet, flow direction, temporal scale, and local conditions. We observe integrated H+ enthalpy fluxes that differ by factors of 3–4 between satellites, even over ion inertial length scales. We observe strong differences in behavior between H+ and O+ enthalpy fluxes in all events, highlighting the importance of species‐specific energization mechanisms. We find tailward‐earthward asymmetry in H+ enthalpy flux, possibly indicative of the influence of the closed earthward boundary of the magnetotail system. Frequency filtering of the Poynting flux shows that current sheet surface waves and structures on the timescale of current sheet flapping contribute significantly, while large‐scale structure contributions are relatively small. We observe that the direction and behavior of the Poynting flux differs between bands, indicating that the observed flux originates from multiple distinct sources or processes. Key Points: Integrated energy fluxes vary significantly depending on satellite position with respect to the X line and plasma sheet O+ enthalpy flux can be a significant or dominant contribution to the overall energy flux from the reconnection region Plasma sheet surface waves and drivers of sheet flapping are the primary sources of Poynting flux